PREDICTION OF FUNCTIONAL DISORDERS OF PANCREAS AND BILIARY TRACT IN CHILDREN WITH REACTIVE ARTHRITIS - Клименко, В.А.; Савво, В.М.; Яновська, К.О. (World of Medicine and Biology, 2014)
Clinical and laboratory characteristics of the pancreas and liver in children with reactive arthritis have been defined. The children were divided by age, and assigned into three age groups. Complaints, findings of physical examination, data of blood chemistry, ultrasound, coprogram have been evaluated. Ultrasound examination of the abdomen was carried out on an empty stomach and with a load of food to determine the functional state of the pancreas. Adverse criteria were developed, which proved possible functional pancreas and liver disorders in children with reactive arthritis.
Keywords: reactive arthritis; children; pancreas; liver